Experimental Study on the Mechanical Properties and Seepage Characteristics of Red Sandstone with a Single Persistent Joint under Triaxial Compression. (17th May 2021) - Wang, Wei; Liu, Shifan; Shi, Chong; Zheng, Shanxi; Zhu, Qizhi
Abstract : In this research, the conventional triaxial compression experiments for intact red sandstone specimens and the specimens with a single persistent joint at different inclination angles, i.e., 0°, 30°, 45°, and 90°, were conducted at first. Based on the results of the conventional tests, the effects of the confining pressure and the joint inclination angle on the mechanical properties including deformation behavior and strength parameters were summarized and analyzed, respectively. We find that the strength and deformation of jointed red sandstone are enlarged due to the increment of confining pressure, and the mechanical parameters of specimens show a U-shaped development with the rise of the joint angle. Besides, to investigate the effects of the pore pressure on seepage characteristics of rocks with joint angles at 0°, 45°, and 90°, a series of triaxial compression drainage tests on the jointed red sandstone were performed. The results show that the pore pressure has a weakening effect on the strength of jointed specimens, which can reduce the strengthening effect induced by confining pressure. Meanwhile, the tested specimens mostly present shear failure modes. As a result, the mechanical responses, seepage characteristics, and cracking modes in red sandstone containing a single persistent joint under triaxial compression are revealed.